Answer:
Explanation:
Given the function
y = —⅔x + 7
The domain of the function is
The input,
x = { -12, -6, 3, 15}
When x = -12 what is y
y = —⅔x + 7
y = — ⅔ × — 12 + 7
Note that, - × - = +
y = 8 + 7
y = 15
Then, when x = -12, y = 15
When x = -6
y = —⅔x + 7
y = — ⅔ × — 6 + 7
Note that, - × - = +
y = 4 + 7
y = 11
Then, when x = -6, y = 11
Also, x = 3
y = —⅔x + 7
y = — ⅔ × 3 + 7
Note that, -×+ = -
y = —2 + 7
y = 5
Then, when x = 3, y = 5
Also, x = 15
y = —⅔x + 7
y = — ⅔ × 15 + 7
Note that, - × + = -
y = — 10 + 7
y = —3
Then, when x = 15 , y = —3
Check attachment
This is one to one mapping
x= -6 y= 11
x= 3 y= 5
x= 15 y= -3
x= -12 y=15